2022
DOI: 10.3390/v14010130
|View full text |Cite
|
Sign up to set email alerts
|

In Acute Dengue Infection, High TIM-3 Expression May Contribute to the Impairment of IFNγ Production by Circulating Vδ2 T Cells

Abstract: γδ T cells are innate cells able to quickly eliminate pathogens or infected/tumoral cells by their antiviral and adjuvancy activities. The role of γδ T cells during Dengue Viral Infection (DENV) infection is not fully elucidated. Nevertheless, human primary γδ T cells have been shown to kill in vitro DENV-infected cells, thus highlighting their possible antiviral function. The aim of this work was to characterize the phenotype and function of Vδ2 T cells in DENV patients. Fifteen DENV patients were enrolled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In DENV-infected patients, we demonstrated that IFN-γ production by γδ T cells was impaired after phosphoantigen stimulation, but they were enriched in perforin. Furthermore, the reduced cytokine release capability may depend on TIM-3 expression, as we demonstrated a negative correlation between the expression of TIM-3 and IFN-γ production by PhAg-stimulated Vδ2 T cells from DENV patients [74].…”
Section: Dengue Virusesmentioning
confidence: 74%
See 1 more Smart Citation
“…In DENV-infected patients, we demonstrated that IFN-γ production by γδ T cells was impaired after phosphoantigen stimulation, but they were enriched in perforin. Furthermore, the reduced cytokine release capability may depend on TIM-3 expression, as we demonstrated a negative correlation between the expression of TIM-3 and IFN-γ production by PhAg-stimulated Vδ2 T cells from DENV patients [74].…”
Section: Dengue Virusesmentioning
confidence: 74%
“…Furthermore, γδ T cells were able to kill DENV-infected targeted DCs and contributed to virus clearance in vivo in a mouse model [73]. In DENV-infected patients, Vδ2 T cells were reduced and expressed high levels of CD38 and HLA-DR [74] activation markers, similarly to NK cells in the first phase of infection [75]. In DENV-infected patients, we demonstrated that IFN-γ production by γδ T cells was impaired after phosphoantigen stimulation, but they were enriched in perforin.…”
Section: Dengue Virusesmentioning
confidence: 99%
“…In acute dengue infection, high TIM-3 but not PD-1 expression contributes to the impairment of IFN-γ production by circulating Vδ2 T cells. 46 Healthy aging and HIV infection independently drive TIGIT and multi-IR expression on γδ T cells.…”
Section: The Heterogeneity Of Exhausted γδ T Cellsmentioning
confidence: 99%
“…γδ T cell activity is also regulated by immune checkpoint receptors, such as program death-1 (PD-1), cytotoxic T-lymphocyte associated protein 4 (CTLA-4), lymphocyte-activation gene 3 (LAG-3), and T cell Immunoglobulin domain and mucin domain 3 (TIM-3) [ 171 , 172 , 173 , 174 ]. Blocking the inhibitory signaling mediated by these receptors with therapeutic monoclonal antibodies (mAbs) has proven beneficial for improving immune responses to refractory malignancies such as melanoma, non-small cell lung cancer, and renal cell carcinoma.…”
Section: Clinical Applications Of Vδ2 T Cell Immunotherapymentioning
confidence: 99%